Virtual data integration for a clinical decision support systems - Intedhar Shakir Nasir; Ayad Hameed Mousa; Sakina M. Ali Alkhafaji; Wafia Shaker Abdul Hussein; Zahraa Razzaq Jasim; Saeed Qasim Ali (Institute of Advanced Engineering and Science, 2023)
Clinical decision support (CDS) supplies clinicians and their patients, and relevant staff with meaningful and timely information intelligently integrated or visualized to enhance health and the health sector. Data is the backbone of decision support systems, especially (clinical) ones. Data integration (either virtual or physical manner) is a powerful technique to manipulate a vast amount of heterogeneous data and prepare it as input for the decision-making process. The difficulties in manipulating data that have a physical data integration technique motivated the decision support developers to tend to data virtualization as a data integration technique. In this paper, a clinical decision support system was developed using the virtual data integration technique. The developed system was evaluated in terms of usability and its capability of providing clinical decision support. The evaluation findings indicate that the proposed system is highly usable and has a positive impact on supporting the clinical decision-making process.